Yield-based drought tolerance index evaluates the drought tolerance of cotton germplasm lines in the interaction of genotype-by-environment - Fenglei Sun; Quanjia Chen; Qin Chen; Menghui Jiang; Yanying Qu (PeerJ, 2023)
Background Cotton is an economically important crop in China, and drought has seriously affected cotton production. Understanding genetic variation, genotype ×environment interactions, and the associations between these traits is critical for developing improved cotton varieties with high drought tolerance. Methods To screen ideal drought-resistant cotton germplasm lines and excellent genotypes, the yield traits of 103 cotton germplasm lines were analyzed. Cotton resource material was planted under normal watering and water deficit conditions for three consecutive years. The yield traits under normal irrigation and water stress conditions were measured, and then five screening indicators were calculated based on the cotton yield per plant under the two water treatments to determine the ideal genotype and most accurate identification indicators. Results The results of correlation analysis and principal component analysis showed that the geometric mean productivity (GMP), mean productivity (MP), and stress tolerance index (STI) were significantly positively correlated with yield under water stress and could be used to distinguish genotypes with high drought tolerance. Among the experimental germplasm lines, some had higher STI and GMP values, indicating their higher drought tolerance. This result indicates that best linear unbiased prediction (BLUP) analysis of the STI and GMP under drought stress can effectively improve screening for drought tolerance in cotton germplasm lines. The results from the screening index, three-dimensional map, and genotype ×environment (GGE) biplots were consistent with the above results. We determined that CQJ-5, Xin lu zao 45, Bellsno, Zhong R 2016 and ND 359-5 are drought-tolerant genotypes that can be used to breed drought-tolerant germplasm lines that produce high and stable yields.